Comparison of the Triage Micro Parasite Panel and Microscopy for the Detection of Entamoeba histolytica/Entamoeba dispar, Giardia lamblia, and Cryptosporidium parvum in Stool Samples Collected in Kenya. (10th July 2012) - Swierczewski, Brett; Odundo, Elizabeth; Ndonye, Janet; Kirera, Ronald; Odhiambo, Cliff; Oaks, Edwin
Abstract : Entamoeba histolytica, Giardia lamblia, and Cryptosporidium parvum are three of the most important parasitic causes of acute diarrhea worldwide. Laboratory diagnosis of these parasites is usually done by ova and parasite examination (O&P examination) via microscopy. The sensitivity and specificity of O&P examination varies among laboratories and can be labor intensive and time consuming. The Triage Micro Parasite Panel (BioSite, San Diego, California) is an enzyme immunoassay kit that can detect E. histolytica/E. dispar, G. lamblia, and C. parvum simultaneously using fresh or frozen stool. The present study evaluated the Triage Micro Parasite Panel in detecting E. histolytica/E. dispar, G. lamblia, and C. parvum compared to O&P examination in 266 stool samples collected at medical facilities in Kenya. The sensitivity and specificity results for the Triage Micro Parasite Panel were: for E. histolytica/E. dispar : 100%, 100%, G. lamblia : 100%, 100% and C. parvum : 73%, 100%. There was no evidence of cross reactivity using the kit with other parasites identified in the stool specimens. These results indicate that the Triage Micro Parasite Panel is a highly sensitive kit that can be used for screening purposes in large scale studies or outbreak investigations or as a possible alternative to O&P examination.